Phase Separation in the Nucleus and at the Nuclear Periphery during Post-Mitotic Nuclear Envelope Reformation - Klizia Maccaroni; Mattia La Torre; Romina Burla; Isabella Saggio (Cells, 2022)
Membrane-enclosed organelle compartmentalization is not the only way by which cell processes are spatially organized. Phase separation is emerging as a new driver in the organization of membrane-less compartments and biological processes. Liquid–liquid phase separation has been indicated as a new way to control the kinetics of molecular reactions and is based on weak multivalent interactions affecting the stoichiometry of the molecules involved. In the nucleus, liquid–liquid phase separation may represent an ancestral means of controlling genomic activity by forming discrete chromatin regions, regulating transcriptional activity, contributing to the assembly of DNA damage response foci, and controlling the organization of chromosomes. Liquid–liquid phase separation also contributes to chromatin function through its role in the reorganization of the nuclear periphery in the post-mitotic phase. Herein, we describe the basic principles regulating liquid–liquid phase separation, analyze examples of phase separation occurring in the nucleus, and dedicate attention to the implication of liquid–liquid phase separation in the reorganization of the nuclear periphery by the endosomal sorting complexes required for transport (ESCRT) machinery. Although some caution is warranted, current scientific knowledge allows for the hypothesis that many factors and processes in the cell are yet to be discovered which are functionally associated with phase separation.